Spatio-temporal analysis of the Permanent Protection Area for municipal environmental management in Parauapebas in the state of Pará-Brazil (Research, Society and Development, 2021)
Igarapé Ilha do Coco, is located in the buffer zone of the Carajás National Forest in the municipality of Parauapebas in the southeastern state of Pará. The present study had as its object of study how the population growth in a municipality in the Amazon is directly related to the in the degradation of a Permanent Protection Area APP; this lack of official delimitation for riparian forests, are factors that directly or indirectly influence the actions of invasion and improper occupation of these legally protected areas, with that there was, over time, a loss of the socio-environmental function of Igarapé Ilha do coco and a stabilization in the degree of degradation continues, followed by a significant recovery of the studied ecosystem.